(untitled) (Research, Society and Development, 2020)
Communication is recognized as a basic condition or activity of human life, which involves more than an exchange of ideas or information. The communication process can trigger positive and negative reactions, depending on the context of who communicates with who receives the communication. The nursing professional must present, as an indispensable and essential competence to be acquired in their professional training, the ability to communicate, as they are the active agent in communicating information to patients and their families. Thus, the present study aims to understand the perception of nurses regarding the communication of difficult news in an emergency care unit in the interior of Minas Gerais. This is a descriptive qualitative case study, carried out with 21 nurses who work in the emergency care unit of a city in the central west of Minas Gerais from February 2015 to February 2016. An interview with a script was carried out semi-structured by the authors. The nurses interviewed showed unpreparedness and lack of knowledge on how to communicate difficult news, considering that it is a medical responsibility. As future work, we hope to develop studies that enable institutions to invest in Permanent Education (EP) programs and for Universities to include this theme in the curriculum of undergraduate nursing courses.